Konstruksi Stereotype Gender Dalam Praktik Pendidikan Anak Usia Dini (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2024)
This research aims to reveal the construction of gender stereotypes manifested in early childhood education practices in educational institutions, especially early childhood education. Using a qualitative approach, this research involved 15 early childhood education teachers selected from five early childhood education institutions located in Darul Imarah District, Aceh Besar. Data was collected through in-depth interviews with class teachers. The results of the research show that there are various perceptions of teachers related to early childhood education that are influenced by gender construction. Some teachers still apply practices that differentiate the treatment between boys and girls, such as the type of games given, the type of punishment applied, as well as expectations for the abilities and interests of each gender. This finding indicates that the gender construction that has been internalized by teachers affects the learning process and the formation of children's gender identity from an early age.Keywords: Construction, gender stereotypes, educational practices, PAUD AbstrakPenelitian ini bertujuan untuk mengungkap konstruksi stereotipe gender termanifestasi dalam praktik pendidikan anak usia dini di lembaga pendidikan, khususnya PAUD. Menggunakan pendekatan kualitatif, penelitian ini melibatkan 15 orang guru PAUD yang dipilih dari lima lembaga PAUD yang berlokasi di Kecamatan Darul Imarah, Aceh Besar. Data dikumpulkan melalui wawancara mendalam dengan guru kelas. Hasil penelitian menunjukkan adanya beragam persepsi guru terkait pendidikan anak usia dini yang dipengaruhi oleh konstruksi gender. Beberapa guru masih menerapkan praktik yang membedakan perlakuan antara anak laki-laki dan perempuan, seperti jenis permainan yang diberikan, jenis hukuman yang diterapkan, serta ekspektasi terhadap kemampuan dan minat masing-masing gender. Temuan ini mengindikasikan bahwa konstruksi gender yang telah terinternalisasi oleh guru mempengaruhi proses pembelajaran dan pembentukan identitas gender anak sejak usia dini. Kata Kunci: Konstruksi, streotype gender, praktik pendidikan, PAUD